Myanmar's engagement in regional integration: Status and way forward - Prabir De (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2017)
Recent restoration of democracy in Myanmar is one of the most important developments in the country's history and potentially of large significance for the region. Owing to its strategic position, Myanmar connects Asia's three big markets - Association of Southeast Asian Nations (ASEAN), China, and India. Since 2011, Myanmar has embarked on a path of political and economic reforms, paving the way for unlocking the country's large potential. Myanmar's underdeveloped infrastructure, unavailability and mismatching of skilled human resources and poor connectivity with neighbouring countries seriously limit Myanmar's participation in the regional and global economies. This non-technical paper discusses Myanmar's participation in regional integration initiatives and argues that greater integration with the neighbours would be of paramount importance in building the country's infrastructure and setting it on the faster growth path.
Keywords: F10; F15; F60; 330; Myanmar; Trade; Regional Integration; WTO; ASEAN; GSP